Understanding the roles of deputy school heads in primary schools in Botswana - Mhlauli, Mavis Bashingie (Advances in Social Sciences Research Journal, 2018)
The position of deputy school head has in recent years attracted the attention of researchers and debate globally (Cranston, 2007). Deputies, in their individual capacity or collectively working with other members of the school management, perform a variety of tasks that contribute to the day-to-day operation of the school. As would be expected, they work very closely with school heads, who have increased delegation of responsibility to deputy heads (Kwan & Walker, 2008). In Botswana as in other countries, deputy school heads play a very significant role in the management of schools. They are actively involved in a broad range of school responsibilities that include the function of head of academics and those delegated to them by school heads. In spite of the significance of their leadership and management school functions, their perspective of the role and responsibilities they perform have not been subjected to any extensive research. This exploratory study sought the views of primary deputy school heads about their role and responsibilities as members of the school management team. The study adopted heuristic case study design and semi-structured interviews were used to collect data. The sample of the study consisted of fifty deputy school heads. Data were analysed inductively using themes. The findings of the study show that they are aware of what their duties entail. The conclusion drawn from the study is that deputy-school heads are overwhelmed with duties that are not part of their job description. The study recommends that their duties be confined mainly to their job description to give them more time to focus on the supervision of teaching and learning, which is their core business. The findings of the study have implications for research and practice.